Prospective Study of Ultrasound Markers of Organ Congestion in Critically Ill Patients With Acute Kidney Injury - William Beaubien-Souligny; Laura Galarza; Brian Buchannan; Vincent I. Lau; Neill K.J. Adhikari; Jean Deschamps; Emmanuel Charbonney; André Denault; Ron Wald (Kidney International Reports)
Introduction: Organ congestion may be a mediator of adverse outcomes in critically ill patients with severe acute kidney injury (AKI). The presence of abnormal venous Doppler waveforms could identify patients with clinically significant organ congestion who may benefit from a decongestive strategy. Methods: This prospective multicenter cohort study enrolled patients with severe AKI defined as Kidney Disease: Improving Global Outcomes stage 2 or higher. Patients were not eligible if they received renal replacement therapy (RRT) for more than 72 hours at the time of screening. Participants underwent serial Doppler ultrasound examinations of the portal, hepatic and intrarenal veins during the week following enrolment. We calculated the venous excess ultrasound (VExUS) score based on these data. The primary outcome studied was major adverse kidney events at 30 days (MAKE30) defined as death, RRT dependence, or a persistent decrease in kidney function. Results: A total of 125 patients were included for whom 291 ultrasound assessments were performed. Severely abnormal venous waveforms were documented in 14.4% of portal vein assessments, 6.5% of intrarenal venous assessments, and 14.4% of hepatic vein assessments. The individual ultrasound markers were not associated with MAKE30. The VExUS score (grade 0–1: reference; grade 2: adjusted hazard ratio [aHR]: 4.03, confidence interval [CI]: 1.81–8.99; grade 3: aHR: 2.70, CI: 1.10–6.65; P = 0.03), as well as severely abnormal portal, hepatic and intrarenal vein Doppler were each independently associated with mortality. Conclusion: Although not significantly associated with MAKE30, venous Doppler abnormalities suggestive of venous congestion were associated with higher mortality in critically ill patients with severe AKI.